The life, death, and afterlife of the record store : a global history - Arnold, Gina; Dougan, John M.; Feldman-Barrett, Christine Jacqueline; Worley, Matthew (Bloomsbury Academic, 2023)
"The first academic, book-length, global look at the record store"--
Keywords: Record stores : History; Record stores : Social aspects; Sound recordings : Collectors and collecting; Sound recording industry